Investigating Medical Parallels between Two Works of Mythology and Epics; Ferdosi’s Shanameh from Iran and Fēng Shén Yǎn Yì from China - eyhane Ahansazan; Amir Hooman Kazemi; Mehrdad Karimi; Hamed Ahansazan (Journal of Research on History of Medicine, 2016)
Some believe that ancient mythological and literary texts solely aimed to amuse and entertain, and were sprouted from their feelings and thoughts, and do not regard the study of the ancient and mythological stories as having the definiteness and clarity which science is known for it. Hence, this is why mythological stories in reality convey the beliefs, nature, attitudes and the extent of human knowledge at some point in history. They account for one of the most important signs of civilization and an important factor in creating cultural ties and dominance in the past. It is on this basis that literature is considered as a symbol of cultural competence and civilization of various nations. Although Ferdosi’s Shanameh from Iran and Fēng Shén Yǎn Yì from China are independent works, numerous similarities in various fields including mythological and medical elements are to be found. It can be concluded that the effects of each of these works have acknowledged the signs of old historical relations between Iran and China.